Current treatment practices and prognostic factors in early-stage ovarian cancer - an analysis of the NOGGO/JAGO - Heublein, Sabine; Baum, Joanna; Jaeger, Anna; Grimm-Glang, Donata; Olthoff, Julia; Braicu, Elena Ioana; Azzam Nieto, Osama; Haßdenteufel, Kathrin; Schmalfeldt, Barbara; Hanker, Lars; Wallwiener, Markus; Schneeweiss, Andreas; et al. (Cancers, 2023)
Background: Surgery is the backbone of early-stage ovarian cancer (OC) management. However, in practice, there is disagreement about the extent of surgical staging and whether additional adjuvant treatment should be provided. As omitting relevant diagnostic or therapeutic procedures might lead to undertreatment, we aimed to structurally investigate treatment practice in addition to prognostic factors in a multicentre series of patients (pts) diagnosed with early-stage OC. Patients: Within this retrospective, multicentre study, medical records of 379 pts who had undergone surgery for suspected early-stage OC between January 2014 and March 2020 were analysed. Results: Of the 379 patients, 292 had pT stage 1a-2a and had complete data on the extent of surgical staging. At least one surgical step was omitted in 100 pts (34.2%). Complete surgical staging (n = 192; (65.8%)) was more often performed in high-grade serous OC and was independent of the healthcare level of the hospital where the initial diagnosis was made. Missing to take peritoneal biopsies was associated with reduced relapse-free-survival in incompletely staged, pT1 cases (p = 0.03). About every second patient (46.7%) with a final stage lower than FIGO IIB and treated with adjuvant chemotherapy received combination chemotherapy. BRCA1 and BRCA2 testing was only performed in a subset of pts, and mutations were detected in 18% (14/79) and 9% (7/85) pts, respectively. Conclusions: This study helps to increase our understanding of early-stage OC treatment and prognosis. In addition to treating patients in compliance with current guidelines, the need for BRCA testing should also be considered for early-stage OC.